Study of Abrasive Wear of Railway Welding Steel Repair, Grade R260 - Srikarun, Buntoeng; Petchsang, Salita; Muangjunburee, Prapas (Princess of Naradhiwas University Journal, 2021)
The purpose of this research was to investigate an abrasive wear of the railway steel grade R260 that had not been repaired and one that had been repaired by shielded metal arc welding (SMAW). The covered electrodes used were DIN 8555: E1-UM-350. There were 3 different brands to compare. The chemical composition, microstructure, hardness, wear test, and worn surface of railway steel and repaired weld metals were investigated. The results presented that the railway steel grade R260 without repaired contained pearlite matrix while the repaired weld metal by covered electrodes A, B, and C exhibited grain boundary ferrite and bainitic structure being added. Besides, the hardness values did not follow the wear resistance. The railway steel showed the highest wear resistance, but the lowest hardness. The maximum hardness could be found in the repaired weld metal using covered electrode C compared to other types of the electrode, whereas its wear resistance was minimum. In addition, the worn surface mechanism of the railway steel and the repaired weld metal by covered electrode A was mainly micro cutting. On the other hand, the repaired weld metal by covered electrode B and C resulted in micro ploughing and micro fracture. Therefore, the cover electrode brand A showed the most suitable for repaired welding of railway steel grade R260.